Analysis of Bending Strength of Composite Materials in Bipolar Plates for Fuel Cell Technology - Zarmawan, Husri; Iswandi, Iswandi; Hermanto, Tino; Darianto, Darianto; Hermawan, Indra; Idris, Muhammad; Jufrizal, Jufrizal; Rahmad Aldori, Yopan (Universitas Medan Area, 2025)
This study aims to this study was to examine the effect of polypropylene (PP) plastic and activated carbon (AC) composition in a plastic composite material. The composite material was mixed using an internal mixer at a processing temperature of 220°C and a speed of 50 rpm. The mixture was then molded with dimensions of 100 mm in length, 15 mm in width, and 2,5 mm in thickness. The sample molding was performed using a compression molding method with a pressure of 1500 MPa at 250°C and a holding time of 300 minutes. Subsequently, the samples were cut according to the bending test dimensions following ASTM D790-03 standards, with dimensions of 100 mm x 12.7 mm x 2.5 mm. The test results for the polypropylene-activated carbon composite in the first composition showed a maximum stress point of 36.95 MPa and an elastic modulus of 4.3096 MPa, while the second composition showed a maximum stress point of 34.58 MPa and an elastic modulus of 3.371 MPa. These findings indicate that increasing the activated carbon composition in polypropylene polymer results in a reduction in bending strength.